2010
DOI: 10.1353/dem.0.0096
|View full text |Cite
|
Sign up to set email alerts
|

Parenting as a “package deal”: Relationships, fertility, and nonresident father involvement among unmarried parents

Abstract: Fatherhood has traditionally been viewed as part of a "package deal" in which a father's relationship with his child is contingent on his relationship with the mother. We evaluate the accuracy of this hypothesis in light of the high rates of multiple-partner fertility among unmarried parents using the Fragile Families and Child Wellbeing Study, a recent longitudinal survey of nonmarital births in large cities. We examine whether unmarried mothers' and fathers' subsequent relationship and parenting transitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
159
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(179 citation statements)
references
References 42 publications
15
159
5
Order By: Relevance
“…Future studies to identify additional strategies to involve young fathers in adolescent prenatal programs are needed. The literature indicates involvement of unmarried young fathers diminishes over time, particularly if the parents' romantic relationship ends (Waller & Swisher, 2006;Tach, Mincy, & Edin, 2010). In our study, participants' romantic involvement with their partners showed no significant change from baseline to postpartum, although the proportion of adolescents living with their partners and the proportion of married couples significantly increased.…”
Section: Discussioncontrasting
confidence: 53%
“…Future studies to identify additional strategies to involve young fathers in adolescent prenatal programs are needed. The literature indicates involvement of unmarried young fathers diminishes over time, particularly if the parents' romantic relationship ends (Waller & Swisher, 2006;Tach, Mincy, & Edin, 2010). In our study, participants' romantic involvement with their partners showed no significant change from baseline to postpartum, although the proportion of adolescents living with their partners and the proportion of married couples significantly increased.…”
Section: Discussioncontrasting
confidence: 53%
“…Our results cast some light on the notions that marriage is a “package deal” and that men “exchange children” when they remarry (Furstenberg & Cherlin, 1991; Tach, Mincy, & Edin, 2010). This idea is based on the assumption that men are connected to children primarily through their spouses and partners.…”
Section: Methodsmentioning
confidence: 63%
“…In Appendices 1 and 2, we estimate robustness models for Tables 7 and 8 respectively, adding a proxy for the presence of additional adults in the home to the full models. Child support receipt may be impacted if there is a new romantic partner in the home, as evidence suggests that non-custodial parent contact and payments to non-resident children is likely to decrease (Juby et al , 2007; Nepomnyaschy, 2007; Tach et al , 2010). New relationships may also motivate a family to move, thus we may be concerned that the presence of additional adults in the household is associated with both regularity and our housing outcomes.…”
Section: Resultsmentioning
confidence: 99%